A Long Way Home: First Nations Adoptions and Repatriations - Doran, John (2018)
This dissertation project explores a phenomenon known as the Sixties Scoop and some of its consequences as told by survivors through their own oral testimony. The Sixties Scoop was a period of aggressive adoption of Indigenous children in Canada and the United States in the 1960s. The Sixties Scoop did not happen in a vacuum; it was part of an ongoing attempt at genocide against Indigenous peoples of the Americas. This study is situated within the history in the eastern Maritimes of genocidal attempts towards the Wabanakis, the Indigenous peoples of the Maritimes. First hand accounts of sailors, traders, soldiers, missionaries and settlers describe observations, interactions and policies. The far-reaching effects of The Indian Act, passed in 1876, are also addressed. Survivors of the Sixties Scoop are interviewed in Toronto between 2012 and 2013. Much has been written about Indigenous Research Methodologies, which is discussed in the thesis. Although autoethnography is used in this study the thesis is only partly autoethnographic. Autoethnography was used as a tool to help Sixties Scoop survivors to speak more freely. The method of a scrapbook of memories relating to the adoptive experience (Arts-informed/Indigenous) was also used to help build a relationship with the adoptees that are interviewed. These adoptees expressed many of the same symptoms described by Residential School survivors. These are the symptoms recognized as post-traumatic stress disorder. Some of the experiences these adoptees relate are long-term depression, recurring suicidal thoughts, a feeling of worthlessness and abandonment, chronic tiredness and a marked tendency to sabotage relationships. These experiences are coupled with a seeming irreparable sense of loss and broken relationships with both birth and adoptive families and communities. These adoptees feel their voices have not been heard and have difficulty finding a place to call their own. Ph.D.